الجامعة وطلبتها من ذوي الإحتياجات الخاصة أي مسؤولية مجتمعية؟ - عروج, فضيلة (جامعة الوادي - University of Eloued, 2019)
تهدف الدراسة الحالية إلى تسليط الضوء على جهود جامعة العربي بن مهيدي –أم البواقي –فيما يخص التكفل بالطلبة من ذوي الإحتياجات الخاصة، باعتبارها فئة هشة تأمل بان تحظى بمبدأ تكافؤ الفرص على غرار الطلبة العاديين، وذلك باستفادتها من الخدمات النفسية والإجتماعية والصحية كنوع من المسؤولية المجتمعية للجامعة تجاه هذه الفئة، ويتعلق الأمر بتفعيل خلية وساطة ومساعدة نفسية واجتماعية لفائدة الطلبة من ذوي الإحتياجات الخاصة محاولين بذلك تقييم دور هذه الخلية وإبراز أهم الصعوبات التي تحول دون تقديم الأفضل.The current study aims to shed light on the efforts of the University of Al-Arabi Bin Mahidi - Umm Al-Bouaghi - with regard to sponsoring students with special needs, as it is a vulnerable group that hopes to have the principle of equal opportunities similar to ordinary students, by making use of psychological, social and health services as a kind of social responsibility The university has a right to this category, and it comes to activating a cell of mediation and psychological and social assistance for the benefit of students with special needs, trying to thus evaluate the role of this cell and highlight the most important difficulties that prevent the provision of the best.
The university and its students with special needs, what social responsibility?
مقال
Keywords: الطلبة من ذوي الإحتياجات الخاصة، المسؤولية المجتمعية للجامعة، خلية وساطة.; students with special needs, university social responsibility, mediation cell.